E-Buletin Arshad Ayub Graduate Business School, UiTM Shah Alam edisi Bil.5/2020 April - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2020)
e-Buletin Arshad Ayub Graduate Business School, UiTM Shah Alam